The effect of swallowing disorder on quality of life in patients with Parkinson’s disease - Bingöl, Dilara; Bengisu, Serkan; Tüfekçioğlu, Zeynep; Demirsoy, Ecem Nur; Hanağası, Haşmet; Topbaş, Seyhun (The European Research Journal, 2025)
Objectives: The aim of this study is to evaluate the severity of dysphagia in Idiopathic Parkinson's Disease (IPD) using both self-assessment and clinical assessment tools, to investigate the correlation between these methods, and to examine the effect of dysphagia on quality of life. Methods: Patients diagnosed with IPD who applied to the Movement Disorders Clinic of the Neurology Department of Istanbul University Faculty of Medicine between 2020-2021 were included in the study. Dysphagia severity was assessed using the Eating Assessment Tool (EAT-10), Dysphagia Disability Index (DHI), and Gugging Swallowing Screening (GUSS). The effect of dysphagia on quality of life was assessed using the Turkish Swallowing Quality of Life Questionnaire (T-SWAL-QOL). Results: A total of 38 patients, 24 (63.2%) of whom were male, were included in the study. There was a moderate correlation between GUSS and EAT-10 scores (r: -0.548; P